Effect of Anolyte on S. Typhimurium and L. monocytogenes Growth in Minced Pork and Beef Cuts - Reda Riešutė; Joana Šalomskienė; Alvija Šalaševičienė; Irena Mačionienė (Foods, 2022)
In this paper, anolyte is considered as a possible disinfectant for inhibiting the growth of bacteria in meat (beef cuts and minced pork). Meat cuts were contaminated with two concentrations of L. monocytogenes and S. Typhimurium, as these are the most common meat pathogens that are closely regulated by the EU, and treated with two different concentrations of anolyte: 20% for beef cuts and 18% for minced pork. Then, the total viable count (TVC), L. monocytogenes count and S. Typhimurium count were determined. In meat cuts and minced pork, anolyte was able to reduce TVC, S. Typhimurium and L. monocytogenes counts effectively, significantly decreasing L. monocytogenes and S. Typhimurium counts after spraying and throughout 29 days of incubation at 0–4 °C. TVC was reduced after spraying and for 10 days of incubation but later increased to be the same as before spraying with anolyte. Anolyte was effective when spraying beef cuts with a 20% solution for 60 s against pathogenic bacteria L. monocytogenes and Salmonella spp. and also when using it at a concentration of 18% from the minced meat mass. Initially, anolyte significantly decreased TVC, however during the storage period (10–29 days) TVC increased but remained significantly lower compared to control. Anolyte was effective in reducing L. monocytogenes and S. Typhimurium counts throughout the study, and after 29 days of incubation, these bacteria could not be detected in the samples treated with anolyte.